Growth and yield of sweet corn (Zea mays L. Saccharata) as affected by incubation time of preparation for tithonia (Tithonia diversifolia) enriched liquid organic fertilizer. Issue 1 (January 2021) - Puteri, A R; Setyowati, N; Fahrurrozi; Muktamar, Z
Abstract: The use of organic fertilizers could be an alternative for synthetic fertilizer because of its high price and limited availability. Organic fertilizer is commonly found in the form of solid or liquid organic fertilizer (LOF). Tithonia ( Tithonia diversifolia ), a broadleaf weed containing high N, P, and K, is often used to enrich LOF. However, the quality of LOF is highly dependent on the incubation time. This study aimed to examine the influence of LOF incubation time on sweet corn plant growth and yield. This experiment was conducted at the Experiment Station, Faculty of Agriculture, University of Bengkulu, from August to December 2019. The experiment used a completely randomized design (CRD), with five treatments and five replications. The treatments were LOF prepared for four, five, six, and seven weeks of incubation. No LOF was allocated as control. The result showed that the incubation time for LOF preparation had no significant effect on plant height, the number of leaves, stem diameter, ear weight, and ear length of sweet corn. It is suggested that the preparation of Tithonia enriched LOF be incubated for four weeks.